The Implementation of Electronic Transfer of Freehold Title in Land Sale and Purchase Transaction at Bogor Regency Land Office - Khasanah, Khasanah; Bhudiman, Budy; Mustika, Desty Anggie (JURNAL MAHASISWA YUSTISI, 2023)
The purpose of this research is to analyze the implementation of the process of electronic transfer of freehold title in land transaction at Bogor Regency Land Office. The main objective of this research is to identify the processes, constraints and benefits associated with the implementation of an electronic transfer of title system in land sale transaction. The research method is a descriptive analytical approach by collecting data through interviews with relevant parties and analyzing documents. The results show that the implementation of electronic transfer of freehold title has made a positive contribution to the process of land transaction, especially in Bogor Regency. It was found that the use of electronic system has improved administrative efficiency, reduced data input errors, and accelerated the processing time of transferring name. Nevertheless, there are still some obstacles related to access to technology. Therefore, the Ministry of Land and Spatial Planning and Bogor Regency Land Office should continue to update the system regularly to speed up the land services. In addition, the process of registering the transfer of rights/reversal of name of certificate is declarative or administrative, not constitutive. This means that the registration of a transfer of title is aimed at giving broader evidentiary powers to third parties in general, but it is not used to establish the validity of the transfer itself. The transfer of rights has occurred since the deed of transfer was signed by the PPAT. This is in contrast to the constitutive function of registration in Western law, where registration creates a new legal situation by determining when the transfer of rights occurs.